Analysis of the Dynamic Relationship of Inflation of Goods / Services Commodities in Central Kalimantan Province - Fany Aprianti (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2022)
This research aims to find out and analyze the dynamic relationship between inflation and commodity groups of goods and services in Central Kalimantan Province. This type of research is quantitative with research methods using the Vector Error Correction Model (VECM) model. Data processing is done using the EViews Version 10 Application. The results of this study show that between Inflation and Commodity Goods / Services there is a dynamic relationship seen from the positive and negative trend movements of variables in each period. There is also a cointegration relationship or long-term relationship between variables meaning that each movement of the inflation average in a given year will affect the movement of the average in the following year. And there is also a causality relationship or two-way reciprocal relationship between Sandang Commodities and Food Commodities, Inflation and Educational Commodities, Recreation and sports, Sandang commodities and Finished Food Commodities, Beverages, Cigarettes and tobacco. This means that every movement of one commodity has an effect on the other commodity.